2014
DOI: 10.1044/2014_ajslp-14-0040
|View full text |Cite
|
Sign up to set email alerts
|

Nonword Repetition in Children With Cochlear Implants: A Potential Clinical Marker of Poor Language Acquisition

Abstract: Purpose Cochlear implants (CIs) can facilitate the acquisition of spoken language for deaf children, but challenges remain. Language skills dependent upon phonological sensitivity are most at risk for these children, so having an effective way to diagnose problems at this level would be of value for school speech-language pathologists. The goal of this study was to assess whether a nonword repetition (NWR) task could serve that purpose. Method 104 second graders participated: 49 with NH and 55 with CIs. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 54 publications
10
61
0
Order By: Relevance
“…Our results revealed that MLU of CI children lags behind that of NH children up to age 6, but CI children caught up by age 7. This is in accordance with for instance Szagun [4], Schauwers [25], Ouellet, Le Normand and Cohen [26], Szagun [27], Nittrouer, Caldwell-Tarr, Sansom, Twersky and Lowensthein [28] and Nittrouer, Sansom, Low, Rice and Caldwell-Tarr [29], who all found lower MLU in CI children as compared to NH children. However, our results show that CI children have age-appropriate MLU scores by age 7.…”
Section: Syntagmatic Developmentsupporting
confidence: 91%
“…Our results revealed that MLU of CI children lags behind that of NH children up to age 6, but CI children caught up by age 7. This is in accordance with for instance Szagun [4], Schauwers [25], Ouellet, Le Normand and Cohen [26], Szagun [27], Nittrouer, Caldwell-Tarr, Sansom, Twersky and Lowensthein [28] and Nittrouer, Sansom, Low, Rice and Caldwell-Tarr [29], who all found lower MLU in CI children as compared to NH children. However, our results show that CI children have age-appropriate MLU scores by age 7.…”
Section: Syntagmatic Developmentsupporting
confidence: 91%
“…In a longitudinal study of children in Australia who used cochlear implants and digital hearing aids, Ching, Day, and Cupples [71], as well as Cupples et al [72], found that phonological awareness was a significant predictor of reading at age five, after controlling for receptive vocabulary and nonverbal cognitive ability. A number of more recent studies [73,74] have also suggested phonological skills as the key to reading for young children who are d/Dhh. As testament to the primacy of the role of phonology in learning to read, various interventions have been designed to facilitate the auditory access to English phonology through visual means for d/Dhh students.…”
Section: Phonological Processing In Word Recognitionmentioning
confidence: 99%
“…Studies by Nittrouer and colleagues (Nittrouer, Caldwell-Tarr, Sansom, Twersky, & Lowenstein, 2014; have highlighted the fact that, in spite of impressive gains in English language for many children who receive cochlear implants, phonological skills still lag behind. Our findings are consistent with this picture.…”
Section: The Marked Improvements In English Vocabulary Evident In Thementioning
confidence: 99%